Micro converter with a high step-up ratio to drive a piezoelectric bimorph actuator applied in mobile robots. (9th April 2018) - Xu, Ziming; Wang, Yiding; Chen, Chen
In this study, a micro converter for driving a piezoelectric actuator is designed and implemented. The converter can produce 100 V, 80 Hz AC voltage from 3.7 V DC voltage. With regard to the requirements of micro mobile robots, the main contributions of this study are the design and implementation of a circuit topology supplying power for micro mobile robots at low power and the miniaturization of this topology to make it suitable for driving a centimeter-level robot. The 91 mg mass (excluding printed circuit board mass), 14 × 12 × 4 mm size, and 84.6% efficiency of the converter indicate that this circuit could be applied in micro mobile robots driven by piezoelectric actuators.